(untitled) (International Journal of Engineering and Computer Science, 2016)
Now a day’s phishing attack has become one of the most serious issues faced by internet users, organizations and service providers. In phishing attack attacker tries to obtain the personal information of the users by using spoofed emails or by using fake websites or both. The internet community is still looking for the complete solution to secure the internet from such attacks. This paper presents an overview about various phishing attacks and various techniques to protect the information from the phishers.